Study on Current Renewable Energy Scenario in India (International Journal of Food and Nutritional Sciences, 2022)
Energy, as a strategic commodity, plays a critical role in every country's social and economic growth. Renewable energy sources have the potential to play a critical role in meeting energy demands. The majority of India's electricity is generated using traditional energy sources such as coal and mineral-based power plants, which contribute significantly to greenhouse gas emissions. Fossil fuels will become scarcer over the next several decades, resulting in energy shortages, rising energy costs, and energy insecurity. Increased usage of fossil fuels also harms the environment by emitting greenhouse gases. As a result, it is necessary to improve energy security while also lowering greenhouse gas emissions. As a result, capturing renewable energy has become a need in today's world. This study examines India's recent renewable energy situation. The current state of renewable energy, national renewable energy policies, and other difficulties and concerns are all covered in-depth in this article. This study helps to understand the Indian scenario of renewable energy as well as its important role.